Evaluation of the AMPLICOR CMV test for direct detection of cytomegalovirus in plasma specimens. - Hiyoshi, M (1997)
We evaluated the AMPLICOR CMV test (PCR) for the direct detection of cytomegalovirus in plasma. Sixty-eight specimens were involved for the comparison between the AMPLICOR test and the antigenemia assay. The sensitivities, specificities, and positive and negative predictive values were 97.1, 100, 100, and 97.1%, respectively, for the AMPLICOR test and 79.4, 100, 100, and 82.9%, respectively, for the antigenemia assay.